2008
DOI: 10.1016/j.jhazmat.2007.07.055
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of air pollution control residues produced in a municipal solid waste incinerator in Portugal

Abstract: This study is mainly related with the physical and chemical characterization of a solid waste, produced in a municipal solid waste (MSW) incineration process, which is usually referred as air pollution control (APC) residue. The moisture content, loss on ignition (LOI), particle size distribution, density, porosity, specific surface area and morphology were the physical properties addressed here. At the chemical level, total elemental content (TC), total availability (TA) and the leaching behaviour with compli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
53
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 80 publications
9
53
0
8
Order By: Relevance
“…Quina et al reported BET surface areas between 4.9-6.8m 2 /g for five separate collections of semi-dry APC residues, from a Portuguese EfW incinerator over a two year period (Quina et al 2008b). The variability in the specific surface area of residue collected from a single facility over time was therefore much smaller than that observed for residues collected from different sites.…”
Section: Characterisation Of As-received Residuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Quina et al reported BET surface areas between 4.9-6.8m 2 /g for five separate collections of semi-dry APC residues, from a Portuguese EfW incinerator over a two year period (Quina et al 2008b). The variability in the specific surface area of residue collected from a single facility over time was therefore much smaller than that observed for residues collected from different sites.…”
Section: Characterisation Of As-received Residuesmentioning
confidence: 99%
“…(Baciocchi et al 2009;Cappai et al 2012;De Boom and Degrez 2012;Dyer et al 2006;Geysen et al 2004b;Li et al 2007;Quina et al 2008b;Wang et al 2010). Residue properties vary not only between facilities but also over time when collected from a single facility (Environment Agency 2002;Quina et al 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…Air pollution control (APC) residues produced in incineration plants are classified as hazardous solid waste mainly due to its high alkaline pH, high content in volatile heavy metals and soluble salts, and trace amounts of very toxic compounds such as dioxins and furans (Quina et al 2008b). The current APC disposal methods in use are very limited, and in the near future they are likely to become unsustainable, due to stringent environmental regulations.…”
Section: Dustmentioning
confidence: 99%
“…Thus, according to measurements in diverse European incinerators, the limit of 0.5 mg/Nm 3 is usually complied (BREF, 2006). Lead and chromium are currently the most problematic heavy metals found in APC residues that lead to a classification as hazardous waste (Quina et al, 2008b).…”
Section: Other Heavy Metalsmentioning
confidence: 99%
“…This method has advantages, such as substantial reduction in volume and mass. In order to apply the method in a large scale, there are fundamental parameters such as fuel behavior in thermal degradation, energy contents and its chemical reactions that should be in place so as to assist designers to come up with an appropriate method of waste energy recovery and disposal system (M.J. Quina et al, 2008).…”
mentioning
confidence: 99%